2005
DOI: 10.1634/stemcells.2004-0021
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface and Transcriptional Characterization of Human Adipose‐Derived Adherent Stromal (hADAS) Cells

Abstract: Adult human subcutaneous adipose tissue contains cells with intriguing multilineage developmental plasticity, much like marrow-derived mesenchymal stem cells. Putative stem or progenitor cells from fat have been given many different names in the literature, reflecting an early and evolving consensus regarding their phenotypic characterization. The study reported here used microarrays to evaluate over 170 genes relating to angiogenesis and extracellular matrix in undifferentiated, early-passage human adipose-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
330
4
6

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(362 citation statements)
references
References 32 publications
22
330
4
6
Order By: Relevance
“…Both cell types express CD105, CD73, CD90 and lack the haematopoietic lineage markers c-kit, CD14, CD11b, CD34, CD45, CD79, CD19 and HLA-DR. These markers are considered the minimal prerequisite to describe MSC (Katz et al, 2005;Schaffler and Buchler, 2007). In 2006, MSC were defined by the International Society for Cellular Therapy as a plastic-adherent cell population with the following surface marker profile: CD13 + , CD44 + , CD90 + , CD73 + and CD105 + , CD14 − , CD11b − , CD79 − , CD34 − , CD45 − and HLA-DR − (Dominici et al, 2006).…”
Section: The Potential Of Msc To Improve the State Of The Artmentioning
confidence: 99%
“…Both cell types express CD105, CD73, CD90 and lack the haematopoietic lineage markers c-kit, CD14, CD11b, CD34, CD45, CD79, CD19 and HLA-DR. These markers are considered the minimal prerequisite to describe MSC (Katz et al, 2005;Schaffler and Buchler, 2007). In 2006, MSC were defined by the International Society for Cellular Therapy as a plastic-adherent cell population with the following surface marker profile: CD13 + , CD44 + , CD90 + , CD73 + and CD105 + , CD14 − , CD11b − , CD79 − , CD34 − , CD45 − and HLA-DR − (Dominici et al, 2006).…”
Section: The Potential Of Msc To Improve the State Of The Artmentioning
confidence: 99%
“…Also, haematopoietic cells were derived using mouse adipose tissue-derived stroma vascular fraction (Charriere et al, 2003;Cousin et al, 2003). Studies were undertaken to characterize ADSCs; these reports showed that the phenotype and genotype at a transcriptional level are quite similar to those of BMSCs (DeUgarte et al, 2003;Katz et al, 2005). However, differentiation potentials might be different.…”
Section: Bone Marrow-derived Stromal Stem Cellsmentioning
confidence: 99%
“…ASCs were isolated as previously described [17,18]. Briefly, samples were washed, enzymatically dissociated, and filtered to remove debris [18].…”
Section: Isolation and Culture Expansion Of Human Adipose Stem Cells mentioning
confidence: 99%